2018
DOI: 10.3390/en11010216
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization: Modeling, Final Properties Design and Applications: A Review

Abstract: Active research on biomass hydrothermal carbonization (HTC) continues to demonstrate its advantages over other thermochemical processes, in particular the interesting benefits that are associated with carbonaceous solid products, called hydrochar (HC). The areas of applications of HC range from biofuel to doped porous material for adsorption, energy storage, and catalysis. At the same time, intensive research has been aimed at better elucidating the process mechanisms and kinetics, and how the experimental var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 111 publications
(263 reference statements)
1
89
0
4
Order By: Relevance
“…Hydrothermal carbonization (HTC) is a thermochemical process converting biomass into lignite‐like products (hydrochar), which takes place in water under subcritical conditions . The combination of temperatures between 180 °C and 250 °C and pressures between 20–80 bars forms a process that replicates the natural process of coal generation.…”
Section: Potential Developments In Closing Of Materials Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal carbonization (HTC) is a thermochemical process converting biomass into lignite‐like products (hydrochar), which takes place in water under subcritical conditions . The combination of temperatures between 180 °C and 250 °C and pressures between 20–80 bars forms a process that replicates the natural process of coal generation.…”
Section: Potential Developments In Closing Of Materials Cyclesmentioning
confidence: 99%
“…Hydrothermal carbonization (HTC) is a thermochemical process converting biomass into lignite-like products (hydrochar), which takes place in water under subcritical conditions. 75,[167][168][169][170] The combination of temperatures between 180 °C and 250 °C 171 and pressures between 20-80 bars 161 forms a process that replicates the natural process of coal generation. During the process, both biomass and water are heated in a pressurized reactor for several hours, which reduces the hydrogen and oxygen contents of the feed and increases its carbon content and energy density.…”
Section: Process Description Of Hydrothermal Carbonization (First Step)mentioning
confidence: 99%
“…In the literature, the definition of reaction time (or residence time) is not uniform. Often, HTC reaction time starts to be counted when the set HTC temperature is reached, while in some other cases [48,49] it includes the time for reactor heating. In this paper, we considered the HTC residence time as the time the reactor is maintained at the set-point constant temperature.…”
Section: Htc Reactor Heat-up Transient Phasementioning
confidence: 99%
“…Still, charcoal, biochar and activated carbon contain particles (e.g., condensates) that can be classified as soot [1]. There is increasing research interest in hydrochar that is suggested as a biofuel, as an adsorbent in soil and water, as well as a catalyst or for energy storage [10]. Thus, there is a considerable overlap of potential applications of hydrochar with those of biochar, activated carbon and charcoal.…”
Section: Pyrogenic Carbonaceous Materials (Pcm): Brief History and Dementioning
confidence: 99%
“…Thus, there is a considerable overlap of potential applications of hydrochar with those of biochar, activated carbon and charcoal. However, due to fundamental differences in history, production process and technology as well as both physical and chemical structure, hydrochar is not discussed in this review [10,11].…”
Section: Pyrogenic Carbonaceous Materials (Pcm): Brief History and Dementioning
confidence: 99%